Economic Analysis of Wind Farm Feasibility in Nigerian Defence Academy, Afaka Kaduna. - Mary Samuel; Muhammad, S.U.; Solomon, W.C.; Japheth, G.C. (Academy Journal of Science and Engineering)
One of the renewable energy sources, wind energy, has grown into a global power generation business that competes with other energy sources. While interest and investments in wind energy recycling systems are steadily rising around the world, scientific researches and commercial activities in this subject are growing day by day. Some economic problems relating to the wind energy obtained by a modeled wind turbine was used to verify the feasibility of a wind farm in NDA that is intended for future energy source in the Academy.